Peran Kegiatan Keagamaan dalam Proses Rehabilitas Anak di Lembaga Pembinaan Khusus Anak - Zubaidah Zubaidah; Cici Presillia; Septya Pransisca; Monika Arbaini (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Juvenile inmates face moral challenges due to past delinquency and lack of guidance. Religious programs in correctional settings offer potential for rehabilitation, yet their role remains underexplored. Objective: This study explores the role of religious guidance in rehabilitating juvenile inmates at LPKA. It aims to analyze the implementation process, behavioral changes, and factors influencing religious guidance programs. Method: A qualitative descriptive approach was used, involving 10 informants. Data were collected through interviews, observations, and documentation. Result: Findings indicate that daily religious activities, including Qur’an recitation, congregational prayers, religious lectures, and dhikr, contribute significantly to behavioral improvements. Juvenile inmates exhibited a transition from negative traits (harsh language, indifference, and misconduct) to positive behaviors (politeness, care for parents, and peaceful interactions). Conclusion: Religious activities play a crucial role in fostering moral and behavioral transformation among juvenile inmates. Self-motivation, family support, staff, and religious mentors serve as supporting factors, while self-resistance and peer influence act as challenges. Contribution: This research underscores the importance of religious guidance as an effective rehabilitation tool, providing valuable insights for policymakers, educators, and social workers in designing more effective rehabilitation programs for juvenile inmates.